Elements of teaching - Salandanan, Gloria G. (Quezon City, Philippines : Lorimar Publishing, Inc., 2012)
In this second revision, a chapter on observing and evaluating teaching Chapter II was included in order that teachers, students, administrators, and parents would be informed how teaching is evaluated for purposes of improving this important mission. From its title, the main focus is on the qualities considered essential to the teaching profession as well on the teacher. Ethics, order, and professionalism are inherent in the teaching profession. Commitment, patience and compassion are innately exhibited by the teacher.
Foreword -- Preface -- Acknowledgement -- The Teaching Profession -- Aptitudes for Teaching -- Elements Inherent in the Teaching Profession -- The Professional Teacher -- Elements Inherent in the Teacher -- Innovative Qualities -- Observing and Evaluating -- Rewards of Teaching -- Growth -- Afterwards -- Endnotes -- Bibliography -- Appendices -- New Teacher Education Curriculum -- Code of Ethics for Professional Teachers.
Includes bibliographical references.
Keywords: TEACHING -- EFFECTIVE TEACHING